Stable isotope (δD–δ18O) relationships of ice facies and glaciological structures within the mid-latitude maritime Fox Glacier, New Zealand. Issue 75 (4th July 2017) - Appleby, John R.; Brook, Martin S.; Horton, Travis W.; Fuller, Ian C.; Holt, Katherine A.; Quincey, Duncan J.
ABSTRACT: Relationships between stable isotopes (δD–δ 18 O), ice facies and glacier structures have hitherto gone untested in the mid-latitude maritime glaciers of the Southern Hemisphere. Here, we present δD–δ 18 O values as part of a broader study of the structural glaciology of Fox Glacier, New Zealand. We analyzed 94 samples of δD–δ 18 O from a range of ice facies to investigate whether isotopes have potential for structural glaciological studies of a rapidly deforming glacier. The δD–δ 18 O measurements were aided by structural mapping and imagery from terminus time-lapse cameras. The current retreat phase was preceded by an advance of 1 km between 1984 and 2009, with the isotopic sampling and analysis undertaken at the end of that advance (2010/11). Stable isotopes from debris-bearing shear planes near the terminus, interpreted as thrust faults, are isotopically enriched compared with the surrounding ice. When plotted on co-isotopic diagrams (δD–δ 18 O), ice sampled from the shear planes appears to show a subtle, but distinctive isotopic signal compared with the surrounding clean ice on the lower glacier. Hence, stable isotopes (δD–δ 18 O) have potential within the structural glaciology field, but larger sample numbers than reported here may be required to establish isotopic contrasts between a broad range of ice facies and glacier structures.